The impact of the media in shaping the Political culture of university youth A field Study - Zreka, Yosra; Abularouss , Rima (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
In the midst of the ongoing revolutions on the level of communication ,Technology , the reflection of that on the events in the communities and the media play an important role in shaping the Political culture of a large number of university youth who get their information from these means and adopt views, positions and tendencies about different topics, according to their reading, their observations and through following the electronic media in all the spheres. The current research deals with the impact of electronic media in shaping the political culture of university youth. And to achieve the objectives of the research a questionnaire was designed and applied on students of the French language, geographical , sociology and philosophy departments. We ended up with the following results: There is statistical significance between the use of electronic media and the formation of political attitudes among university youth. There is statistical significance between the use of electronic media and the motives of this use among university youth. There is statistical significance between the impact of electronic media on the political tendencies of university students and its association with their sex.